Intervención urbana del humedal Voltezuela como lugar ecoturístico en el municipio de Garzón Huila - Jiménez Chala, Estefanía; Trujillo Vargas, Estefanía (Universidad Antonio Nariño, 2023)
After an analysis carried out on the importance of wetlands, it was necessary to cover problems found in the area, the abandonment and misuse that the development of cities and the different unused uses have generated problematic recordings of environmental losses. In this, the economic, social and environmental study begins to improve the ecosystem of the lagoon la voltezuela located in the municipality of Garzon-Huila. The advantages in the wetland area begin to be characterized by wanting to give the community landscape areas accompanied by research and recreational spaces, thus wanting to provide Educational, Environmental, economic and social support through the objectives of sustainable development.